Impact of behavioral change on the epidemic characteristics of an epidemic model without vital dynamics - Jianquan Li; Xiaoqin Wang; Xiaolin Lin (Mathematical Biosciences and Engineering)
The epidemic characteristics of an epidemic model with behavioral change in [V. Capasso, G. Serio, A generalizaition of the Kermack-McKendrick deterministic epidemic model, Math. Bios., 42 (1978), 43-61] are investigated, including the epidemic size, peak and turning point. The conditions on the appearance of the peak state and turning point are represented clearly, and the expressions determining the corresponding time for the peak state and turning point are described explicitly. Moreover, the impact of behavioral change on the characteristics is discussed.